Mediation effect of cognitive flexibility between fear of negative evaluation and interaction anxiety - AVCU, AKİF (My University, 2023)
Social anxiety has an increasing pattern during adolescence and is common among university students. It is associated with many adverse outcomes. Although there is considerable progress in social anxiety literature, there are signifcant gaps, and more research is needed to clarify causal pathways and moderator and mediator efects. This study evaluated the mediating role of cognitive fexibility in the link between fear of negative evaluation and interaction anxiety, which are two main symptom clusters of social anxiety. The sample comprised 552 undergraduate university students, 453 (82.1%) female and 99 (17.9%) male and 4 (0.7%) unspecifed, from various departments. The study used self-report measures. Results showed that the fear of negative evaluation is signifcantly related to interaction anxiety, and cognitive fexibility demonstrates a partial mediation efect in this relationship. These fndings contribute to the current literature by revealing cognitive fexibility as a mediator between fear of negative evaluation and interaction anxiety. The results suggest that working on cognitive fexibility may help prevent the development of interaction anxiety in university students.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; Social anxiety; Fear of negative evaluation; Interaction anxiety; Cognitive fexibility; University students; Mediation model